Urgent issues and prospects in correctional rehabilitation practice and research. (15th February 2022) - Ward, Tony; Arrigo, Bruce; Barnao, Mary; Beech, Anthony; Brown, Deirdre A.; Cording, Jacinta; Day, Andrew; Durrant, Russil; Gannon, Theresa A.; Hart, Stephen D.; Prescott, David; Strauss‐Hughes, Annalisa; et al.
Abstract: The aim of this paper is to identify some of the urgent issues currently confronting criminal justice policymakers, researchers and practitioners. To this end a diverse group of researchers and clinicians have collaborated to identify pressing concerns in the field and to make some suggestions about how to proceed in the future. The authors represent individuals with varying combinations of criminal justice research, professional training (e.g. social work, criminal justice, criminology, social work, clinical psychology) and clinical orientation, and experience. The paper is comprised of 13 commentaries and a subsequent discussion based on these reflections. The commentaries are divided into the categories of explanation of criminal behaviour, clinical assessment and correctional intervention, and cover issues ranging from the role of clinical expertise in treatment, problems with risk assessment to the adverse effects of social oppression on minority groups. Following the commentaries, we summarize some of their key themes and briefly discuss a number of major issues likely to confront the field in the next 5–10 years.